Ugly Affective Politics in “Yambunera” by Bina Theeng - Tamang, Anju (Mindscape: A Journal of English & Cultural Studies, 2023)
This paper studies affective politics generated by ugly feelings such as fear, contempt, and shame in the characters of the story “Yambunera” written by Bina Theeng from anthology of stories named Yambunera. The first part of this paper emphasizes on ugly feeling and affective politics as the major theoretical framework. Affect theory has evolved from studying emotions to using these emotions to analyze different aspects of human life, even nature. Ugly feelings are also called negative feelings which are related to emotions. The study investigates how these negative emotions are created, circulated and politicized. The second part is examination and interpretation of the characters of “Yambunera” through the negative feelings generated in them due to the state’s brutality and discrimination. The state is the major agency of rule and control that suppresses minority communities through different mediums will the major discussion of this part. This paper explores the state’s treatment on indigenous communities which has created negative feelings in the members. The state needs to provide basic needs and rights to all citizens. However, in the context of Nepal, the state has been using different methods of exploitation and suppression of native nations though it is a multicultural country.